A writer's guide to active setting [how to enhance your fiction with more descriptive, dynamic settings] - Buckham, M. E. (Mary Elizabeth) 1956-; Love, Dianna (Cincinnati, Ohio Writer's Digest Books, 2015)
"A Writer's Guide to Active Setting will show you how to create vivid, detailed settings that bring your story to life. You'll learn how to deepen character development, anchor readers to a specific time and place, reveal backstory without slowing things down, elevate action sequences, and more. Drawing upon examples from authors writing across a variety of genres, Mary Buckham illustrates exactly how the proper use of setting can dramatically improve your story" -- provided by publisher.
Subtitle from cover.
Includes bibliographical references (pages 239-242) and index.
Keywords: Setting (Literature); Fiction -- Authorship; Fiction -- Technique